A new three-dimensional dynamic model and experimental validation for motion of a part in a vibratory bowl feeder. (January 2020) - Najmi, Sayedemadodin; Karimi, Amir Hossein; Shadmani, Mohammad; Ziaei-Rad, Saeed
Highlights: Presenting a 3D dynamic model for motion of a part on a vibratory bowl feeder. Deriving equations of motion of the part in the sliding and hopping regimes. Proposing an algorithm for the numerical solution of the equations of motion. Carrying out an experimental campaign on a prevalent bowl feeder. Comparing the results of the numerical solution and experimental measurements. Abstract: In this research, dynamics of a part in a vibratory bowl feeder is studied. So far, studies have been done in two dimensions which is an inaccurate approximation to the 3D part motion. Hence, a new dynamic model is introduced for motion of the part under the effect of base excitation which is moving on or separating from a 3D spiral track. Different scenarios which may occur due to the interaction of the part and the track such as sliding and hopping are predicted. The equations of motion of the part are derived for each scenario and a solution algorithm is presented. The system of equations is solved numerically to obtain the position of the part as a function of time. To validate the proposed dynamic model and the numerical solution, experimental tests are carried out. Good agreement between the results of these methods demonstrates the accuracy of this model. It is observed that the excitation frequency would greatly affect the motion of the part. For low excitation frequencies, the only mechanism involved in the motion of the part is the sliding one. By increasing the excitation frequency, the major driving mechanism changes to hopping.